2009
DOI: 10.4049/jimmunol.182.3.1696
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Mediates a Reduced Expression of the Activating Receptor NKG2D in NK Cells from End-Stage Renal Disease Patients

Abstract: To characterize the immune defect of patients with end-stage renal disease (ESRD), we performed NK cell subset analysis in 66 patients with ESRD treated by hemodialysis (n = 59) or peritoneal dialysis (n = 7). Compared with healthy blood donors, patients undergoing chronic dialysis showed a profound decrease in NKG2D+ cells within both the CD8+ T cell (58% vs 67%, p = 0.03) and NK cell (39% vs 56%, p = 0.002) populations. CD56dim cells, which comprise the majority of NK cells in the periphery, were more affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 54 publications
2
58
0
Order By: Relevance
“…Conversely, oxidative stress has been previously found to induce NKG2DL expression in other cell systems. 27,28,41 These findings highlight the complexity of the molecular mechanisms leading to the induction of different ligands for distinct NK-activating receptors, and further support the notion that they may involve common or distinct pathways depending on the form of stress, the type of ligand, and the cellular context.Our study also shows that monocytes are the main cellular source of ROS that regulate PVR expression during Ag-induced T-cell proliferation. Indeed, we observed reduced levels of PVR on proliferating T cells cultured in the context of CD14 ϩ cell-depleted PBMCs, which were almost completely restored upon addition of H 2 O 2 .…”
mentioning
confidence: 51%
“…Conversely, oxidative stress has been previously found to induce NKG2DL expression in other cell systems. 27,28,41 These findings highlight the complexity of the molecular mechanisms leading to the induction of different ligands for distinct NK-activating receptors, and further support the notion that they may involve common or distinct pathways depending on the form of stress, the type of ligand, and the cellular context.Our study also shows that monocytes are the main cellular source of ROS that regulate PVR expression during Ag-induced T-cell proliferation. Indeed, we observed reduced levels of PVR on proliferating T cells cultured in the context of CD14 ϩ cell-depleted PBMCs, which were almost completely restored upon addition of H 2 O 2 .…”
mentioning
confidence: 51%
“…Given the importance of changes in the endogenous cellular redox for DDR activation in response to several DNA damaging agents including DOX and MEL (27,28,40), and because most studies addressing the role of oxidative stress in the regulation of NKG2D and DNAM-1 ligands rely on the exposure to exogenous sources of ROS (i.e., H 2 O 2 ) or to exogenous exposure of endogenously produced ROS (25,41,42), we tested whether the druginduced activation of DDR cascade underlying the enhancement of MICA, MICB, and PVR expression was dependent on ROS signaling. We demonstrated that DOX-and MEL-dependent change in the redox state is the major event triggering the activation of the DDR pathway and leads to activating NK receptor ligand upregulation on MM cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that various cellular stresses such as reactive oxygen species and DNA damage up-regulate MICA/B expression (Peraldi et al, 2009) and that dysregulated 5 expression of NKG2D ligands is involved in the development of inflammatory and autoimmune diseases such as rheumatoid arthritis, celiac disease and type 1 diabetes (Groh et al, 2003;Meresse et al, 2004;Ogasawara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%